A low-temperature sintering multi-peak copper-based solder paste and its preparation method and application

By adopting low-temperature sintered multimodal copper-based solder paste, using pretreatment of copper powder and adding organic acids and nickel salts, the problems of easy oxidation of copper particles and poor stability of solder paste in copper-based solder paste sintering interconnect technology are solved, and low-temperature sintering interconnection on thermally sensitive substrates are realized, reducing costs and improving the oxidation resistance and high-temperature reliability of solder paste.

CN117001206BActive Publication Date: 2025-04-18JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311157872.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-04-18
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

The existing copper-based solder paste sintering interconnection technology has problems such as easy oxidation of copper particles, poor stability of solder paste, high sintering temperature, high pressure and reducing atmosphere protection, which limits its application in the field of power electronic device packaging.

Method used

A low-temperature sintered multimodal copper-based solder paste was used to pretreat the copper powder, and organic acid and nickel salt were added to form a three-peak copper powder mixture, and low-pressure sintering was carried out in an inert atmosphere to reduce the sintering temperature to 200°C.

Benefits of technology

Low-temperature sintering interconnection on thermally sensitive substrates is realized, cost reduction, oxidation resistance and high-temperature reliability of solder paste are improved, and dependence on high pressure and reducing atmosphere is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004439262070000101
    Figure BDA0004439262070000101
  • Figure BDA0004439262070000111
    Figure BDA0004439262070000111
  • Figure BDA0004439262070000121
    Figure BDA0004439262070000121
Patent Text Reader

Abstract

The present invention discloses a low-temperature sintering multi-peak copper-based solder paste and a preparation method and application thereof. The copper-based solder paste of the present invention is prepared by pre-treating copper powder to obtain a copper powder precipitate, treating it with an organic acid solution or first treating it with an organic acid solution and then treating it with a metal salt, drying it and then grinding it, adding an organic solvent, stirring it, and finally grinding it to homogenize it to obtain a copper-based metal solder paste. The copper-based solder paste and the copper-based solder paste sintering interconnection technology prepared by the present invention can achieve low-temperature sintering interconnection at 200°C, can be used on heat-sensitive substrates such as PCB substrates, and are conducive to expanding the application scenarios of copper solder paste sintering connection technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to copper sintering interconnection technology, and in particular to a low-temperature sintering multi-peak copper-based solder paste and a preparation method and application thereof. Background Art

[0002] Metal particle solder paste sintering interconnection technology is considered to be one of the most promising technologies for achieving high thermal conductivity and high heat resistance mounting of power chips. Compared with traditional solder interconnection technology and transient liquid phase sintering technology, metal particle solder paste sintering interconnection technology not only has high interconnection strength, good electrical and thermal conductivity, but also has good high-temperature reliability. However, the commonly used silver particle solder paste sintering interconnection material is not only costly but also has poor resistance to electrochemical migration. These shortcomings will seriously limit its wide application. On the other hand, although the existing copper particle solder paste is low in cost, due to the high melting point of copper, sintering interconnection technology often requires the use of copper nanoparticles with higher driving force. Copper nanoparticles have a high tendency to agglomerate, and a large amount of dispersants, binders, diluents and other additives need to be added to ensure the printability and stability of copper solder paste, which usually leads to a long sintering time (>60min) and it is difficult to avoid the generation of large cracks in the sintered structure. For interconnection joints, copper nano solder paste sintering interconnection technology usually requires a higher auxiliary pressure.

[0003] In addition, because copper nanoparticles are easily oxidized during preparation and storage, they usually need to be sintered in a reducing atmosphere (hydrogen or formic acid) or the sintering temperature must be increased to above 300°C. These factors make the copper-based solder paste sintering interconnection process extremely complicated and cannot be used on heat-sensitive printed circuit boards (PCBs). Although the use of silver-copper core-shell structure particles can effectively improve the oxidation resistance of copper-based solder paste, its preparation process is complicated and costly. In addition, due to the high energy of the silver-copper core-shell interface, the silver-copper core-shell structure will spontaneously destroy during the high-temperature sintering process, resulting in copper being exposed and oxidized, and the reliability of the sintered interconnection joints is poor.

[0004] In summary, the current copper-based solder paste sintering interconnection technology still has several major problems: 1) copper particles are easily oxidized and the solder paste has poor stability; 2) the sintering interconnection temperature of copper solder paste is high; 3) the copper solder paste sintering interconnection process usually requires a high auxiliary pressure; 4) the copper solder paste sintering interconnection process usually requires reducing atmosphere protection; 5) the high temperature stability (anti-oxidation) of the copper solder paste sintering interconnection structure is poor. These problems seriously limit the promotion and application of copper solder paste sintering interconnection technology in the field of power electronic device packaging. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a low-temperature sintering multi-peak copper-based solder paste and its preparation method and application. The copper-based solder paste and copper-based solder paste sintering interconnection technology proposed in the present invention can achieve low-temperature sintering interconnection at 200°C and can be used on heat-sensitive substrates such as PCB substrates, which is conducive to expanding the application scenarios of copper solder paste sintering connection technology.

[0006] A method for preparing a low-temperature sintering multi-peak copper-based solder paste comprises the following steps:

[0007] (1) pre-treating the copper powder to obtain a copper powder precipitate for standby use;

[0008] (2) adding an organic acid solution to the copper powder precipitate, stirring, and centrifuging to obtain a copper powder precipitate;

[0009] (5) drying the copper powder precipitate obtained in step (2) at 40-55° C. to obtain a dry powder;

[0010] (6) grinding the dried powder obtained in step (5), adding an organic solvent, mixing, and stirring to obtain a copper-based solder paste mixture;

[0011] (7) Grinding the copper-based solder paste mixture and homogenizing the dispersant to obtain a copper-based solder paste.

[0012] In some embodiments, in step (1), the copper powder is pretreated by: dispersing the copper powder in a sulfuric acid solution, stirring to obtain a copper powder suspension, centrifuging, collecting the precipitate, and obtaining a copper powder precipitate.

[0013] In some embodiments, the copper powder includes copper powder A, copper powder B and copper powder C; the mass ratio of copper powder A, copper powder B and copper powder C is 3-9: 0.2-1.4: 0.8-5.6; the copper powder A is a submicron copper particle with a size of 0.1-0.3 μm and an average size of 0.18±0.05 μm; copper powder B is a submicron copper particle with a size of 0.3-1.0 μm and an average size of 0.8±0.1 μm; copper powder C is a micron copper flake with a size of 1.5-5.0 μm and an average size of 2.6±0.2 μm; the concentration of the dilute sulfuric acid is 10%-12%, and the mass ratio of copper powder to sulfuric acid is 1:1-1.2; the centrifugal washing process is: repeatedly centrifuging with water until the upper layer is clear and colorless and transparent, and then centrifuging with anhydrous ethanol.

[0014] In some embodiments, in step (2), the organic acid includes one or two of lactic acid, formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, succinic acid, ascorbic acid, citric acid, and tartaric acid; the mass concentration of the organic acid solution is 25-30%; the mass ratio of the copper powder precipitate to the organic acid is 1:2-3; and the stirring time is 60-120 min.

[0015] In some embodiments, the preparation method further comprises the following steps:

[0016] (3) mixing the metal salt with the solvent to prepare a metal salt solution;

[0017] (4) adding the metal salt solution prepared in step (3) to the copper powder precipitate in step (2), and stirring to obtain a copper-nickel mixture;

[0018] At this time, the copper powder precipitate in step (5) is replaced by a copper-nickel mixture, that is, step (5) is: drying the copper-nickel mixture obtained in step (4) at 40-55° C. to obtain a dry powder.

[0019] In some embodiments, in step (3), the metal salt is a nickel salt, and the nickel salt includes one or more of nickel formate, nickel acetate, nickel carbonate, and nickel oxalate; the mass volume ratio of the metal salt to the solvent is 0.1-0.2:10; and the solvent is anhydrous ethanol.

[0020] In some embodiments, in step (4), the mass ratio of the metal salt to the copper powder precipitate is 1 to 15:100.

[0021] In some embodiments, in step (6), the organic solvent includes one or more of terpineol, ethylene glycol, n-butanol, diethylene glycol, polyethylene glycol 200, polyethylene glycol 300, glycerol, dipropylene glycol methyl ether acetate, 1,3-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine, and the mass ratio of the dry powder to the organic solvent is 86-90:10-14.

[0022] A low-temperature sintering multi-modal copper-based solder paste prepared by the preparation method.

[0023] An application of the low-temperature sintering multi-modal copper-based solder paste, wherein the low-temperature sintering multi-modal copper-based solder paste is used for preparing interconnecting joints and printed circuits.

[0024] In some embodiments, the interconnection joint is obtained by sintering at a pressure of 0 to 20 MPa and an inert atmosphere; the printed circuit is obtained by sintering the copper-based solder paste under no pressure and an inert atmosphere; the inert atmosphere is nitrogen or argon.

[0025] The beneficial technical effects of the present invention are:

[0026] (1) The copper-based solder paste sintering interconnection technology proposed in the present invention can achieve low-temperature sintering interconnection at 200°C and can be used on heat-sensitive substrates such as PCB substrates, which is conducive to expanding the application scenarios of copper solder paste sintering connection technology.

[0027] (2) The present invention uses larger-sized submicron and micron multi-peak copper powders, and uses organic acids to modify the surface of the copper material. The prepared copper solder paste has strong antioxidant properties under room temperature and atmospheric conditions, and the cost is greatly reduced compared to the solution of using silver-coated copper nanoparticle technology to synergistically improve the antioxidant properties of the solder paste.

[0028] (3) The present invention adopts a three-peak copper material composed of submicron particles and micron copper sheets with specific shape, size distribution and mass ratio, which effectively improves the packing density during sintering and inhibits the generation of cracks; at the same time, compared with traditional copper nano solder paste, it has lower cost, lower agglomeration tendency, and high commercial application value.

[0029] (4) The present invention changes the properties of the copper solder paste by adding nickel salt to the copper solder paste, so that nickel or nickel oxide particles are decomposed during sintering and evenly distributed in the bonding layer, forming a strong metallurgical bond with copper, thereby improving the oxidation resistance and high-temperature reliability of the sintered interconnect structure.

[0030] (5) The present invention improves the method of adding nickel salt so that the nickel salt can be evenly attached around the copper material, thereby improving the uniformity of the copper-based solder paste. DETAILED DESCRIPTION

[0031] The present invention will be described in detail below in conjunction with the embodiments.

[0032] The low-temperature sintering multi-modal copper-based solder paste of the present invention mainly consists of trimodal (three main sizes) copper powder surface-modified by lactic acid or ascorbic acid, uniformly dispersed nickel salt, and one or more organic solvent mixtures with reducing properties at high temperatures.

[0033] The present invention uses lactic acid or ascorbic acid to treat copper powder, which can form a copper compound shell layer on the surface of the copper powder, effectively improving the oxidation resistance of the copper powder and the stability of the copper solder paste.

[0034] The present invention adopts copper powders of three specific sizes, shapes and proportions as copper materials, which can reduce the usage of copper nanoparticles, improve the oxidation resistance of copper particles and the stability of solder paste, and at the same time, the filling effect between particles of different sizes and morphologies can effectively increase the packing density of the sintered structure, reduce the porosity, and effectively inhibit the generation of large cracks in the sintered structure, and finally improve the electro-mechanical properties of the sintered structure; the use of a solvent system with reducing properties at high temperature can improve the oxidation resistance during the sintering process, thereby reducing the dependence on the reducing atmosphere.

[0035] The nickel salt component added in the present invention can be decomposed into nickel or nickel oxide during the sintering process and coated on the surface of copper particles, thereby improving the oxidation resistance and high-temperature stability of the sintered structure of the copper-based solder paste during later use.

[0036] Through the synergistic effect of multiple treatments, the low-cost copper-based solder paste obtained by the present invention can achieve efficient sintering interconnection under low temperature (200-280°C) and pressureless (0MPa) / low pressure (<20MPa) inert atmosphere (no reducing atmosphere, such as hydrogen or formic acid) is required. The sintered structure has excellent electro-mechanical properties and high-temperature stability, which can meet the needs of high-temperature and high-power chip mounting and other low-temperature interconnection-high-temperature application scenarios.

[0037] The copper material of the present invention is composed of three kinds of copper powders with specific size distribution and shape: copper powder A is submicron copper particles, with a size distribution range of 0.1-0.3 μm, an average size of 0.18±0.05 μm, and oxidation on the surface; copper powder B is submicron copper particles, with a size distribution range of 0.3-1.0 μm, an average size of 0.8±0.1 μm, and oxidation on the surface; copper powder C is micron copper flakes, with a size distribution range of 1.5-5.0 μm, and an average size of 2.6±0.2 μm. Copper powders of different particle sizes and morphologies cooperate with each other to increase the packing density and reduce the porosity. The combination of two copper powders of the same size or different morphologies cannot achieve the effect of the present application.

[0038] The preparation steps of the copper-based solder paste of the present invention are:

[0039] (1) mechanically mixing three kinds of copper powders according to the mass ratio of copper powder A, copper powder B and copper powder C of 3-9:0.2-1.4:0.8-5.6, dispersing the mixture in a dilute sulfuric acid solution to obtain a mixture of copper powder and dilute sulfuric acid, stirring the mixture in a magnetic stirrer for 30-60 minutes; centrifugally washing the stirred copper powder suspension with deionized water for multiple times until the supernatant is colorless and transparent, and finally centrifugally washing it once with anhydrous ethanol and taking out the copper powder precipitate M for later use;

[0040] (2) adding an organic acid solution diluted with anhydrous ethanol to a concentration of 25% to 30% to the mixed copper powder precipitate M, wherein the organic acid comprises one of lactic acid, formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, succinic acid, ascorbic acid, citric acid, and tartaric acid, or a mixture of the two, and stirring in a magnetic stirrer for 60-120 minutes, wherein the mass ratio of copper powder to organic acid is 1:2-3; washing the stirred copper powder suspension with anhydrous ethanol by centrifugation for multiple times until the supernatant is colorless and transparent, and taking out the copper powder precipitate N for later use;

[0041] (5) placing the copper powder precipitate N obtained in step (2) in a vacuum oven for drying at a temperature of about 40 to 55° C. until the ethanol is completely volatilized to obtain a dry powder (pure copper powder) and cooling to room temperature;

[0042] (6) mechanically grinding the dry powder of step (5), adding an organic solvent for mixing, wherein the organic solvent comprises one or a mixture of terpineol, ethylene glycol, n-butanol, diethylene glycol, polyethylene glycol 200, polyethylene glycol 300, glycerol, dipropylene glycol methyl ether acetate, 1,3-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine, wherein the mass ratio of the dry powder to the organic solvent is 86-90:10-14, and stirring the mixture in a planetary mixer at a speed of 1800-2000 r / min for a stirring time of 10-20 min to preliminarily obtain a copper-based solder paste mixture;

[0043] (7) The copper-based solder paste mixture of step (6) is placed in a three-roll grinder for grinding, dispersion and homogenization. The grinding gap is set to 40 μm for grinding for 2 min, the grinding gap is set to 20 μm for grinding for 2 min, the grinding gap is set to 10 μm for grinding for 4 min, and the grinding gap is set to 5 μm for grinding for 6 min, to finally obtain a copper-based solder paste.

[0044] The present invention also provides another method for preparing a low-temperature sintering multi-peak copper-based solder paste, comprising the following steps:

[0045] Steps (1)-(2) are the same as above;

[0046] (3) fully mixing nickel salt powder and anhydrous ethanol to obtain a nickel salt solution;

[0047] (4) adding the metal salt solution prepared in step (3) to the copper powder precipitate of step (2), and obtaining a uniform copper-nickel mixture L by mechanical stirring, wherein the nickel salt comprises one or a mixture of nickel formate, nickel acetate, nickel carbonate, and nickel oxalate, and the mass ratio of the nickel salt to copper is 1-15:100.

[0048] (5) placing the copper-nickel mixture L obtained in step (4) in a vacuum oven for drying, with the heating temperature set to about 40 to 55° C., until the ethanol is completely volatilized to obtain a dry powder, i.e., a copper-nickel mixed powder, and cooling to room temperature;

[0049] (6) After mechanically grinding the dry powder of step (5), an organic solvent is added for mixing, wherein the organic solvent includes one or a mixture of terpineol, ethylene glycol, n-butanol, diethylene glycol, polyethylene glycol 200, polyethylene glycol 300, glycerol, dipropylene glycol methyl ether acetate, 1,3-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine, wherein the mass ratio of the dry powder to the solvent is 86-90:10-14, and the mixture is stirred in a planetary mixer at a speed of 1800-2000 r / min and a stirring time of 10-20 min to preliminarily obtain a copper-based solder paste mixture;

[0050] (7) The copper-based solder paste mixture obtained in step (6) is placed in a three-roll grinder for grinding, dispersion and homogenization. The grinding gap is set to 40 μm for grinding for 2 min, the grinding gap is set to 20 μm for grinding for 2 min, the grinding gap is set to 10 μm for grinding for 4 min, and the grinding gap is set to 5 μm for grinding for 6 min, to finally obtain a copper-based solder paste.

[0051] In addition, the preparation steps of pressureless sintering interconnection joints and printed circuits using copper-based solder paste are as follows:

[0052] S1-1: Use a steel screen printing method to print the above copper-based solder paste on the surface of a 25×15×1mm copper plate to form six 2mm×2mm×100μm solder paste patterns, then use tweezers to place a 2×2×1mm copper sheet (used as a dummy chip) on the solder paste pattern, and use tweezers to gently press to ensure that the copper sheet is in close contact with the copper solder paste. Finally, place this "sandwich" structure in an inert atmosphere (nitrogen or argon), a heating environment of 200-280°C and a pressure of 0MPa for 3-60min to obtain an interconnection joint.

[0053] S1-2: Print three 20mm×3mm×100um solder paste patterns on a 75×25×1mm glass slide by screen printing or dispensing, and then heat it in an inert atmosphere (nitrogen or argon) at 200 to 280°C for 3 to 60 minutes to obtain a printed circuit board.

[0054] Preparation of copper-based solder paste pressure sintering interconnect joints:

[0055] S2-1: Use a steel screen printing method to print 6 2mm×2mm×100μm solder paste patterns on the surface of a 25×15×1mm copper plate with a copper-based solder paste. Then place the copper plate on a heating table at 150-190°C and preheat and dry it in an inert atmosphere (nitrogen or argon) for 5-30 minutes. After preheating and drying, cool it to room temperature. Use a placement machine to place a 2×2×1mm copper sheet (for a dummy chip) on the solder paste pattern. Finally, place this "sandwich" structure in an inert atmosphere (nitrogen or argon), heat it at 230-280°C and a pressure of 2-20MPa for 2-8 minutes to obtain an interconnection joint.

[0056] Example 1

[0057] A low-temperature sintering multi-peak copper-based solder paste, the preparation method of which is as follows:

[0058] (1) 8 g of copper powder A, 0.5 g of copper powder B and 1.5 g of copper powder C are dispersed in 100 g of a 10% dilute sulfuric acid solution to obtain a mixture of copper powder and dilute sulfuric acid, and the mixture is stirred in a magnetic stirrer for 30 min; the stirred copper powder suspension is centrifuged and washed several times with deionized water until the supernatant is colorless and transparent, and finally centrifuged and washed once with anhydrous ethanol to remove the copper powder precipitate M.

[0059] (2) Pour the precipitate M into 90 g of 25% lactic acid ethanol solution at a mass ratio of 1:2.5 and stir magnetically for 60 min. Wash the stirred copper powder suspension several times by centrifugation with anhydrous ethanol until the supernatant is colorless and transparent, and take out the copper powder precipitate N for later use.

[0060] (3) The copper powder precipitate N was placed in a vacuum oven for drying at a heating temperature of 55° C. until the ethanol was completely evaporated to obtain a dry powder (pure copper powder) and cooled to room temperature.

[0061] (4) The mass ratio of the dry powder to the organic solvent is 88:12. The ground copper powder and 1.36 g of polyethylene glycol 300 solvent are added to a sample bottle, and the mixture is stirred in a planetary mixer at a speed of 1800 r / min for 10 min to preliminarily obtain a copper-based solder paste mixture.

[0062] (5) The obtained copper-based solder paste is placed in a three-roll grinder for grinding, dispersion and homogenization. The grinding gap is set to 40 μm for grinding for 2 min, the grinding gap is set to 20 μm for grinding for 2 min, the grinding gap is set to 10 μm for grinding for 4 min, and the grinding gap is set to 5 μm for grinding for 6 min, to finally obtain the copper-based solder paste.

[0063] (6) The copper-based solder paste is printed on the surface of a 25×15×1mm copper plate by screen printing to form six 2mm×2mm×100μm solder paste patterns. Then, a 2×2×1mm copper sheet (used as a dummy chip) is placed on the solder paste pattern using tweezers. The tweezers are used to gently press the copper sheet to ensure close contact between the copper sheet and the copper solder paste. Finally, the "sandwich" structure is placed in nitrogen and heated to 280°C at a rate of 10°C / min for 30 minutes to obtain an interconnection joint.

[0064] (7) Three solder paste patterns of 20 mm × 3 mm × 100 um were printed on a 75 × 25 × 1 mm glass slide by screen printing, and then placed in nitrogen and heated to 280 ° C at a rate of 10 ° C / min for 30 min to obtain a printed circuit board.

[0065] Embodiments 2 to 8

[0066] Examples 2 to 8 respectively use different parameters to prepare copper solder pastes and sintered interconnects and circuits. The remaining preparation methods and conditions are the same as those of Example 1. The specific parameters are shown in Table 1.

[0067] Example 9

[0068] A low-temperature sintering multi-peak copper-based solder paste, the preparation method of which is as follows:

[0069] (1) 6 g of copper powder A, 0.8 g of copper powder B and 3.2 g of copper powder C are dispersed in 100 g of a 10% dilute sulfuric acid solution to obtain a mixture of copper powder and dilute sulfuric acid, and the mixture is stirred in a magnetic stirrer for 30 min; the stirred copper powder suspension is centrifuged and washed several times with deionized water until the supernatant is colorless and transparent, and finally centrifuged and washed once with anhydrous ethanol to remove the copper powder precipitate M.

[0070] (2) Pour the precipitate M into 90 g of 25% lactic acid ethanol solution at a mass ratio of 1:2.5 and stir magnetically for 60 min. Wash the stirred copper powder suspension several times by centrifugation with anhydrous ethanol until the supernatant is colorless and transparent, and take out the copper powder precipitate N for later use.

[0071] (3) The copper powder precipitate N was placed in a vacuum oven for drying at a heating temperature of 55° C. until the ethanol was completely evaporated to obtain a dry powder (pure copper powder) and cooled to room temperature.

[0072] (4) The mass ratio of the dry powder to the organic solvent is 89:11. The ground copper powder and 1.36 g of polyethylene glycol 300 solvent are added to a sample bottle, and the mixture is stirred in a planetary mixer at a speed of 1800 r / min for 10 min to preliminarily obtain a copper-based solder paste mixture.

[0073] (5) The obtained copper-based solder paste is placed in a three-roll grinder for grinding, dispersion and homogenization. The grinding gap is set to 40 μm for grinding for 2 min, the grinding gap is set to 20 μm for grinding for 2 min, the grinding gap is set to 10 μm for grinding for 4 min, and the grinding gap is set to 5 μm for grinding for 6 min, to finally obtain the copper-based solder paste.

[0074] (6) The copper-based solder paste was printed on the surface of a 25×15×1mm copper plate by screen printing to form six 2mm×2mm×100μm solder paste patterns. The copper plate was then placed on a heating table at 180°C and preheated and dried for 10 min under nitrogen. After preheating and drying, the plate was cooled to room temperature. A 2×2×1mm copper sheet (used as a dummy chip) was placed on the solder paste pattern using a placement machine. Finally, the "sandwich" structure was placed in nitrogen at a pressure of 2MPa and heated to 280°C at a rate of 10°C / min for 2 min to obtain an interconnection joint.

[0075] Example 10

[0076] A low-temperature sintering multi-peak copper-based solder paste, the preparation method of which is as follows:

[0077] (1) 6 g of copper powder A, 0.8 g of copper powder B and 3.2 g of copper powder C are dispersed in 100 g of a 10% dilute sulfuric acid solution to obtain a mixture of copper powder and dilute sulfuric acid, and the mixture is stirred in a magnetic stirrer for 30 min; the stirred copper powder suspension is centrifuged and washed several times with deionized water until the supernatant is colorless and transparent, and finally centrifuged and washed once with anhydrous ethanol to remove the copper powder precipitate M.

[0078] (2) Pour the precipitate M into 90 g of 25% lactic acid ethanol solution at a mass ratio of 1:2, and stir magnetically for 60 min. Wash the stirred copper powder suspension several times by centrifugation with anhydrous ethanol until the supernatant is colorless and transparent, and take out the copper powder precipitate N for later use.

[0079] (3) 0.1 g of nickel formate dihydrate and 10 g of anhydrous ethanol were fully mixed to obtain a nickel formate solution.

[0080] (4) Pour the nickel formate solution into the copper powder precipitate N at a mass ratio of metal salt to copper powder of 10:100 and mechanically stir to obtain a uniform copper-nickel mixture.

[0081] (5) The copper-nickel mixture L was placed in a vacuum oven for drying at a heating temperature of 55° C. until the ethanol was completely evaporated to obtain a dry powder (copper-nickel mixed powder) and cooled to room temperature.

[0082] (6) The mass ratio of the dry powder to the organic solvent is 89:11. The ground copper-nickel mixed powder and 1.24 g of a mixed solvent of polyethylene glycol 300 and pinene alcohol in a ratio of 1:2 are added to a sample bottle. The mixture is stirred in a planetary mixer at a speed of 1800 r / min for 10 min to preliminarily obtain a copper-based solder paste mixture.

[0083] (7) The obtained copper-based solder paste is placed in a three-roll grinder for grinding, dispersion and homogenization. The grinding gap is set to 40 μm for grinding for 2 min, the grinding gap is set to 20 μm for grinding for 2 min, the grinding gap is set to 10 μm for grinding for 4 min, and the grinding gap is set to 5 μm for grinding for 6 min, to finally obtain the copper-based solder paste.

[0084] (8) The copper-based solder paste was printed on the surface of a 25×15×1mm copper plate by screen printing to form six 2mm×2mm×100μm solder paste patterns. The copper plate was then placed on a heating table at 180°C and preheated and dried for 30 min under nitrogen. After preheating and drying, the plate was cooled to room temperature. A 2×2×1mm copper sheet (used as a dummy chip) was placed on the solder paste pattern using a placement machine. Finally, the "sandwich" structure was placed in nitrogen at a pressure of 2MPa and heated to 280°C at a rate of 10°C / min for 30 min to obtain an interconnection joint.

[0085] Examples 11 to 13

[0086] Examples 11 to 13 are the same as Example 10, except that Examples 11 to 13 use different parameters to prepare copper solder paste and sintered interconnect joints, respectively. The specific parameters are shown in Table 1.

[0087] Embodiment 14

[0088] A low-temperature sintering multi-peak copper-based solder paste, the preparation method of which is as follows:

[0089] (1) 6 g of copper powder A, 0.8 g of copper powder B and 3.2 g of copper powder C are dispersed in 100 g of a 10% dilute sulfuric acid solution to obtain a mixture of copper powder and dilute sulfuric acid, and the mixture is stirred in a magnetic stirrer for 30 min; the stirred copper powder suspension is centrifuged and washed several times with deionized water until the supernatant is colorless and transparent, and finally centrifuged and washed once with anhydrous ethanol to remove the copper powder precipitate M.

[0090] (2) Pour the precipitate M into 90 g of 25% lactic acid ethanol solution at a mass ratio of 1:3, and stir magnetically for 60 min. Wash the stirred copper powder suspension several times by centrifugation with anhydrous ethanol until the supernatant is colorless and transparent, and take out the copper powder precipitate N for later use.

[0091] (3) 0.1 g of nickel formate dihydrate and 10 g of anhydrous ethanol were fully mixed to obtain a nickel formate solution.

[0092] (4) Pour the nickel formate solution into the copper powder precipitate N at a mass ratio of metal salt to copper powder of 10:100 and mechanically stir to obtain a uniform copper-nickel mixture.

[0093] (5) The copper-nickel mixture L was placed in a vacuum oven for drying at a heating temperature of 55° C. until the ethanol was completely evaporated to obtain a dry powder (copper-nickel mixed powder) and cooled to room temperature.

[0094] (6) The mass ratio of the dry powder to the organic solvent is 89:11. The ground copper-nickel mixed powder and 1.24 g of a 1:1 mixed solvent of polyethylene glycol 300 and pinene alcohol are added to a sample bottle, and the mixture is stirred in a planetary mixer at a speed of 1800 r / min for 10 min to preliminarily obtain a copper-based solder paste mixture.

[0095] (7) The obtained copper-based solder paste is placed in a three-roll grinder for grinding, dispersion and homogenization. The grinding gap is set to 40 μm for grinding for 2 min, the grinding gap is set to 20 μm for grinding for 2 min, the grinding gap is set to 10 μm for grinding for 4 min, and the grinding gap is set to 5 μm for grinding for 6 min, to finally obtain the copper-based solder paste.

[0096] (8) Three solder paste patterns of 20 mm × 3 mm × 100 um were printed on a 75 × 25 × 1 mm glass slide by screen printing, and then placed in nitrogen and heated to 280 ° C at a rate of 10 ° C / min for 30 min to obtain a printed circuit board.

[0097] Embodiments 15-16

[0098] Examples 15 and 16 are the same as Example 14, except that Examples 15 to 16 use different parameters to prepare copper solder paste and sintered circuits. The process is basically the same as that of Example 14, and the specific parameters are shown in Table 1.

[0099] Table 1 Parameter conditions and sintering conditions of the embodiment

[0100]

[0101]

[0102]

[0103] Embodiment 17

[0104] The method is the same as Example 2, except that in step (3), the metal salt is nickel acetate, and the mass volume ratio of the metal salt to anhydrous ethanol is 0.2:10; in step (4), the mass ratio of the metal salt to the copper powder is 1:100; in step (5), the heating temperature is set to 40°C; in step (6), the mass ratio of the dry powder to the organic solvent is 86:14.

[0105] Embodiment 18

[0106] The method is the same as Example 2, except that in step (3), the metal salt is nickel acetate, and the mass volume ratio of the metal salt to anhydrous ethanol is 0.15:10; in step (4), the mass ratio of the metal salt to the copper powder is 15:100; in step (5), the heating temperature is set to 50°C; in step (6), the mass ratio of the dry powder to the organic solvent is 90:10.

[0107] Comparative Examples 1 to 3

[0108] Since the packing density and sintering driving force are different after mixing the three-peak copper powder in different proportions, the final copper solder paste has different sintering properties. Therefore, Comparative Examples 1 to 3 investigate the preparation of copper-based solder paste and sintered products when changing the proportions of copper powder A, copper powder B and copper powder C in the copper solder paste.

[0109] Comparative Examples 1 to 3 are the same as Examples 1 to 3, except that the ratio and type of copper powder A, copper powder B and copper powder C are changed. The specific parameter settings are shown in Table 2. After sintering, the resistivity and shear strength are tested at room temperature.

[0110] Table 2 Parameters and sintering conditions of Comparative Examples 1 to 3

[0111]

[0112]

[0113] Comparative Examples 4 to 6

[0114] The oxidation degree and surface structure of the copper powder itself have a great influence on the quality of the copper solder paste. Therefore, in Comparative Examples 4 to 6, the copper powder treated with organic acid is replaced with untreated copper powder and copper powder only treated with sulfuric acid for deoxidation, as shown in Table 3. The preparation steps of the copper solder paste and the remaining processes and parameters are the same as those of Examples 6 to 8.

[0115] Comparative Example 7

[0116] At the same time, since different ways of surface modification of copper powder by organic acid will also affect the surface structure of copper particles, in comparative example 7, organic acid and solvent are directly mixed to form copper solder paste, and the remaining steps are the same as those in example 6. The sintering and other parameter settings are shown in Table 3, and the shear strength and resistivity are tested after sintering.

[0117] Table 3 Parameters and sintering conditions of Comparative Examples 4 to 7

[0118]

[0119]

[0120] Comparative Example 8

[0121] The amount of nickel salt added also has a great influence on the quality of the copper solder paste and the oxidation resistance of the sintered layer. Comparative Example 8 changed the amount of nickel salt added (adding excessive nickel salt), and the copper solder paste preparation process and sintering process were the same as Example 14, and the other parameter settings were shown in Table 4. After sintering, the resistivity and resistance change rate were tested.

[0122] Table 4 Parameters and sintering conditions of Comparative Example 8

[0123]

[0124] Comparative Example 9

[0125] Since different ways of adding nickel salts will affect the uniformity of the solder paste, a copper solder paste with completely different properties is finally obtained. Comparative Example 9 is the same as Example 14, except that nickel formate powder is directly added, that is, step (3) is not included, and in step (4), nickel formate powder is added to the copper powder precipitate and stirred to obtain a copper-nickel mixture L, and the sintering parameters are set as shown in Table 5. The remaining processes and parameters are the same as Example 14. After sintering, the resistivity and resistance change rate are tested.

[0126] Table 5 Parameters and sintering conditions of comparative example 9

[0127]

[0128] Test example:

[0129] The copper-based solder pastes prepared in the embodiments of the present invention and the comparative examples were tested for high temperature stability, mechanical properties, and resistance properties. The specific test methods and results are as follows.

[0130] The specific method for evaluating the high temperature stability of the sintered structure of the copper-based solder paste is as follows: the copper-based solder paste prepared in the embodiment and the comparative example is prepared according to the method of step S1-2 to obtain a printed circuit, which is placed on a heating table and placed in a heating environment of 250° C. in air for 60 minutes.

[0131] The resistance of the printed circuit was tested at room temperature using a Uni-T UT61A high-precision multimeter, and the resistance growth rate ((R-R0) / R0, where R is the resistance of the printed circuit obtained by placing the copper-based solder paste prepared in the embodiment and the comparative example according to S1-2 on a heating table and placing it in a heating environment of 250° C. in air for 60 minutes, and R0 is the resistance of the printed circuit obtained by placing the copper-based solder paste prepared in the embodiment and the comparative example according to S1-2).

[0132] The shear strength test method of the interconnection joint is as follows: the copper-based solder paste prepared in the embodiment and the comparative example is used to obtain the interconnection joint according to the methods of S1-1 and S2-1 respectively, and the shear strength test of the obtained interconnection joint is performed at room temperature using a Sigma push-pull tester of Xyztec Company, and the test speed is 1000μm / s.

[0133] The resistivity performance test method of the sintered circuit is as follows: the printed circuit obtained by S1-2 using the copper-based solder paste prepared in the embodiment and the comparative example is tested for resistivity at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., with a probe spacing of 1 mm.

[0134] The test results of Examples 1-16 are shown in Table 6.

[0135] Table 6 Performance test of the embodiment

[0136]

[0137] It can be seen from Table 6 that the resistivity is only about 8.2 to 14.8 μΩ·cm when sintered at 280°C for 30 minutes, the conductivity is good, the shear strength is higher than 40 MPa, and a reliable connection has been formed; although the resistivity in the embodiment with the addition of nickel formate is slightly increased, it still meets the electro-mechanical properties required for the connection, and the resistance change rate is less than 60%, which has excellent high-temperature oxidation resistance.

[0138] The test data of the corresponding products of Comparative Examples 1 to 3 are shown in Table 6.

[0139] Table 7 Performance test of comparative examples 1 to 3

[0140]

[0141]

[0142] As shown in Table 7, compared with Examples 1 to 3, Comparative Example 1 lacks the addition of micron copper at the same sintering temperature, resulting in dense cracks in the sintered copper, which cannot form a circuit, has a very high resistivity, and seriously affects the stability and reliability of the joint; while Comparative Examples 2 and 3 have a reduced sintering drive rate due to the addition of larger-sized micron copper powder C exceeding 50%, and cannot form a good sintered layer at the same temperature, and ultimately the resistivity increases and the joint strength decreases compared with the examples. This shows that the present invention effectively improves the electro-mechanical properties of copper connections by using trimodal copper of a specific size and optimizing the ratio.

[0143] The average resistivity and average shear strength of Comparative Examples 4 to 7 are shown in Table 8.

[0144] Table 8 Performance Tests of Comparative Examples 4 to 7

[0145]

[0146] According to Table 8, compared with Examples 6 to 8, at the same copper powder ratio and sintering time, both the resistivity and shear strength of Comparative Examples 4 to 6 are inferior to the copper solder paste prepared by the copper powder of the present invention at different sintering temperatures and different solvent systems. This proves that the present invention effectively improves the electro-mechanical properties of the copper solder paste for pressure-free connection at low temperature by using organic acid to modify the surface of the copper powder before preparing the copper solder paste.

[0147] The test data of Comparative Example 8 is shown in Table 9.

[0148] Table 9 Performance test of comparative example 8

[0149]

[0150] As shown in Table 9, compared with Examples 14, 15, and 16, as the content of nickel formate added increases, the resistance change rate gradually decreases, but in Comparative Example 8, due to the excessive addition of nickel formate, the initial resistivity becomes extremely high and cannot meet the requirements of industrial applications. This shows that the present invention can effectively improve the stability and oxidation resistance of copper connection by mixing an appropriate amount of nickel formate in the copper solder paste.

[0151] The test data of Comparative Example 9 is shown in Table 10.

[0152] Table 10 Performance test of comparative examples 1 to 3

[0153]

[0154] As shown in Table 10, compared with Example 14, when nickel formate dihydrate is added by mechanical mixing and grinding, the properties of the obtained copper solder paste are greatly different from those of the copper solder paste of the present invention. Since the nickel formate in the comparative example cannot be evenly dispersed around the copper particles, the uniformity of the sintered copper is deteriorated, and finally the resistivity and the annualized resistance change rate are deteriorated. Therefore, the present invention can effectively improve the uniformity of the copper solder paste by optimizing the addition method of nickel formate dihydrate, and finally the sintered copper obtains excellent electro-mechanical properties.

[0155] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A method for preparing a low-temperature sintering multi-peak copper-based solder paste, characterized in that: The steps include: (1) pre-treating the copper powder to obtain a copper powder precipitate for standby use; (2) adding an organic acid solution to the copper powder precipitate, stirring, and centrifuging to obtain a copper powder precipitate; (5) drying the copper powder precipitate obtained in step (2) at 40-55° C. to obtain a dry powder; (6) grinding the dried powder obtained in step (5), adding an organic solvent, mixing, and stirring to obtain a copper-based solder paste mixture; (7) grinding the copper-based solder paste mixture and homogenizing the dispersant to obtain a copper-based solder paste; The copper powder includes copper powder A, copper powder B and copper powder C; the mass ratio of copper powder A, copper powder B and copper powder C is 3-9: 0.2-1.4: 0.8-5.6; the copper powder A is submicron copper particles with a size of 0.1-0.3 μm; the copper powder B is submicron copper particles with a size of 0.3-1.0 μm; the copper powder C is micron copper flakes with a size of 1.5-5.0 μm; In step (6), the organic solvent includes one or more of terpineol, ethylene glycol, n-butanol, diethylene glycol, polyethylene glycol 200, polyethylene glycol 300, glycerol, dipropylene glycol methyl ether acetate, 1,3-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine.

2. The preparation method according to claim 1, characterized in that: In step (1), the copper powder is pretreated by dispersing the copper powder in a sulfuric acid solution, stirring to obtain a copper powder suspension, centrifuging, collecting the precipitate, and obtaining a copper powder precipitate.

3. The preparation method according to claim 2, characterized in that: The average size of the copper powder A is 0.18±0.05μm; the average size of the copper powder B is 0.8±0.1μm; the average size of the copper powder C is 2.6±0.2μm; the concentration of the dilute sulfuric acid is 10% to 12%, and the mass ratio of the copper powder to the sulfuric acid is 1:1 to 1.2; the centrifugation process is: repeatedly centrifuging with water until the upper clear liquid is colorless and transparent, and then centrifuging once with anhydrous ethanol.

4. The preparation method according to claim 1, characterized in that: In step (2), the organic acid includes one or more of lactic acid, formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, succinic acid, ascorbic acid, citric acid, and tartaric acid; the concentration of the organic acid solution is 25-30%; the mass ratio of the copper powder precipitate to the organic acid is 1:2-3; and the stirring time is 60-120 min.

5. The preparation method according to claim 1, characterized in that: The following steps are also included: (3) mixing a nickel salt with a solvent to prepare a nickel salt solution; (4) adding the nickel salt solution prepared in step (3) to the copper powder precipitate in step (2), and stirring to obtain a copper-nickel mixture; At this time, the copper powder precipitate in step (5) is replaced by a copper-nickel mixture, that is, step (5) is: drying the copper-nickel mixture obtained in step (4) at 40-55° C. to obtain a dry powder.

6. The preparation method according to claim 5, characterized in that: In step (3), the nickel salt includes one or more of nickel formate, nickel acetate, nickel carbonate, and nickel oxalate; the mass volume ratio of the metal salt to the solvent is 0.1-0.2:10; and the solvent is anhydrous ethanol.

7. The preparation method according to claim 5, characterized in that: In step (4), the mass ratio of the metal salt to the copper powder precipitate is 1 to 15:

100.

8. The preparation method according to claim 1, characterized in that: In step (6), the mass ratio of the dry powder to the organic solvent is 86-90:10-14.

9. A low-temperature sintering multi-modal copper-based solder paste prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the low temperature sintering multi-modal copper-based solder paste according to claim 9, characterized in that: Used for preparing interconnection joints and printed circuits; the interconnection joints are obtained by sintering at a pressure of 0 to 20 MPa and an inert atmosphere; the printed circuit is obtained by sintering the copper-based solder paste under a pressure-free, inert atmosphere; the inert atmosphere is nitrogen or argon.

Citation Information

Patent Citations

  • Copper soldering paste, copper soldering paste preparation method and chip

    CN112238310A

  • Solder powder, method for manufacturing same, and method for preparing solder paste using this powder

    WO2017104562A1